The Qur’anic intertextuality in Maroun Abboud’s critical discourse - Sayad, Siham (Journal of Human Sciences, 2021)
The screams of modern criticism call for the removal of the boundaries between the creative text and the critical text. This latter has ceased to present itself with a discourse that dominates the scepter of power and has a denial in his language, to a transcendent discourse that defies the literary creativity in its peculiarities and that is language and fiction. The critical discourse has proved that it is like all the other discourses, especially the literary ones because it writes with its memory that memorizes texts, images, voices and echoes piled together.However, the critical discourse has become like a carnival as described by Bakhtin - and because MarounAbboud’s critical discourse was a space or a theater for accommodating absent texts and a diverse textual coexistence, especially the Qur’anic text, which was a colorful phenomenon. We considered pursuing this phenomenon by criticizing MarounAbboud for observing these forms, which varied between interaction and textual transcendence with the Qur’an.